Computer aided design, engineering and manufacturing of bicycle brake arm / Mazrul Akmal Mustapha and Aza Murdiana Wan Mustapha - Mustapha, Mazrul Akmal; Wan Mustapha, Aza Murdiana (2004)
Chapter 1 is an introduction of bicycle brake arm and also CAD/CAM. In this chapter also the objective, scope of work, significant of project and methodology is explained. Chapter 2 is the story on theoretical analysis of bicycle brake arm while chapter 3 is about CAD/CAE/CAM of bicycle brake arm. In chapter 4, the comparison between theoretical analysis and finite element analysis is made. The steps involved in CNC manufacturing is explained in chapter 5. In chapter 6, discussion is made regarding to the result. Lastly, in chapter 7, conclusion highlighted our achieving from bicycle brake arm project while recommendation is made towards the improvement in future.